Zgodovina vakuumske metalurgije - Južnič, Stanislav (Vakuumist, 2000)
The articles surveys the development of knowledge about the physical properties of metals before the 20th century in the lands inhabited by Slovens. Tha main part of our work describes the European and American research of vacuum metallurgy until the 1950s, except the vacuum evaporation/sputterin processes, which are alredy described in previous numberof this journal.
Keywords: vakuumska tehnika; vakuumska metalurgija; zgodovinski pregledi